Trend Analysis of Stunting Prevalence in West Java (2019-2024) Using WHO Thresholds - Beatrice, Florentia; Tatsbita, Ghaisha Izzati; Indrayana, Ayesha Qabila Ramazani; Yanuar, Alfarizi Haunan; Nurshiyam, Dini; Maulana, Rafeyfa Ashyla Putri; Kamila, Mutiara Shofa; Aprilia, Lia; Anggraeni, Salwa; Ilham, Nur Indah Khairunnisa Kurniawaty; Arafah, Safila Siti; Purwandi, Avicenna Ihyal Faza; Hidayat, Yuyun (International Journal of Mathematics, Statistics, and Computing, 2025)
This study aims to analyze the trend of stunting prevalence among children under five across various cities and regencies in West Java Province during the 2019–2024 period using a simple linear regression approach. The data utilized in this study are secondary data obtained from official local government sources, along with the stunting classification standards established by the World Health Organization (WHO). The results indicate that 40% of regions showed statistically significant declines, such as Indramayu Regency, Bekasi City, and Karawang Regency. Conversely, 60% of the regions showed a decrease in stunting rates that was not statistically significant, including Cirebon City and Garut Regency. The variation in the coefficient of determination (R²) highlights differences in model strength across regions, while the p-value suggests that not all downward trends can be considered statistically significant. These findings are expected to serve as a basis for formulating more targeted and effective interventions to reduce stunting prevalence in West Java Province.